DSP controlled isolated DC-DC converter for distributed generation system - Younis M.A.A.; Rahim N.A.; Mekhilef S. (Praise Worthy Prize S.r.l, 2023)
This paper presents the analysis and design of Isolated DC-DC converter suitable for distributed generation system. The DC-DC converter consist H-bridge inverter, High frequency transformer, full bridge rectifier, and low pass filter. Phase shift PWM with Zero voltage and zero current switching used to minimize the switching power dissipation. Digital Signal Processing (DSP) board is used to implement the control algorithm. The control algorithm includes phase-shift PWM and PID close loop control, are designed using SIMULINK Embedded Target Library which are used to represent algorithms and peripherals specific DSP family. The converter is simulated using SIMULINK software to verify the operation of the converter. Fuel cell model is prepared to act as unstable voltage source in the simulation of the converter. Experimental results and simulation results are shown to validate the proposed DC-DC converter. 2011 Praise Worthy Prize S.r.l. - All righs reserved.